Influenza‐like illness as a trigger for ischemic stroke. Issue 4 (14th March 2018) - Boehme, Amelia K.; Luna, Jorge; Kulick, Erin R.; Kamel, Hooman; Elkind, Mitchell S. V.
Abstract: Objective: We hypothesized that ILI is associated with risk of incident stroke, and that the risk would be highest closest in time to the event. Methods: This case‐crossover analysis utilized data obtained from the California State Inpatient Database of the Healthcare Cost and Utilization Project (HCUP). The outcome of interest was ischemic stroke. Exposure was defined as a visit to the emergency department or hospitalization for influenza‐like illness (ILI) 365, 180, 90, 30, or 15 days before stroke (risk period) or similar time intervals exactly 1 or 2 years before stroke (control period). Conditional logistic regression was used to calculate the odds ratio and 95% confidence interval (OR, 95% CI). Results: In 2009, 36, 975 hospitalized ischemic strokes met inclusion criteria, and of these strokes, 554 (1.5%) had at least 1 episode of ILI in the 365‐day risk period prior to their stroke. Using non‐overlapping time intervals from ILI to stroke, the odds of ischemic stroke was greatest in the first 15 days post ILI (OR: 2.88, 95% CI: 1.86–4.47). The strength of the relationship decreased as the time from ILI increased, and was no longer significant after 60 days. There was a significant interaction ( P = 0.017) with age and ILI; the odds of stroke associated increased 7% with each 10‐year decrease in age (OR per 10‐year age decrease 1.07, 95% CI: 1.03–1.35). Interpretation: We found that ILI increases short‐term risk of stroke, particularly in people under the age of 45, and therefore may be considered to act as a trigger for stroke.